2018
DOI: 10.5792/ksrr.17.073
|View full text |Cite
|
Sign up to set email alerts
|

Open Posterior Approach versus Arthroscopic Suture Fixation for Displaced Posterior Cruciate Ligament Avulsion Fractures: Systematic Review

Abstract: PurposeTo compare the clinical outcomes between the open posterior approach and arthroscopic suture fixation for displaced posterior cruciate ligament (PCL) avulsion fractures.MethodsA literature search was performed on MEDLINE, EMBASE, and the Cochrane Library databases. The inclusion criteria were as follows: papers written in English on displaced PCL avulsion fractures, clinical trial(s) with clear description of surgical technique, adult subjects, a follow-up longer than 12 months and modified Coleman meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Multiple studies have shown that the Lysholm scores improved significantly pre‐ and postoperatively, from 36.5 to 95.0, respectively 17,19–21 . Similarly, we confirmed that the median Lysholm knee score increased from 40.4 preoperatively to 90.1 postoperatively.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Multiple studies have shown that the Lysholm scores improved significantly pre‐ and postoperatively, from 36.5 to 95.0, respectively 17,19–21 . Similarly, we confirmed that the median Lysholm knee score increased from 40.4 preoperatively to 90.1 postoperatively.…”
Section: Discussionsupporting
confidence: 85%
“…Three recent papers which are in agreement with our results have reported reaching a preinjury level of activity, and all patients returned to their previous levels or sports. 1,17,18 The preinjury score averaged 7.1, while the postoperative score averaged 6.8. Multiple studies have shown that the Lysholm scores improved significantly pre-and postoperatively, from 36.5 to 95.0, respectively.…”
Section: Clinical Outcomes Of the Arthroscopic Direct Anteriorto-post...mentioning
confidence: 99%
“… 1 Both open and arthroscopic procedures have been reported, and similar clinical results have been obtained. 2 , 3 Regarding open procedures, the fixation is direct and simple and there is no need for the learning curve of arthroscopic surgical procedures, 4 , 5 , 6 , 7 but these procedures are invasive. The advantage of arthroscopic procedures 8 , 9 , 10 is that the fracture can be directly exposed intra-articularly and combined intra-articular lesions can be treated simultaneously, in addition to their minimally invasive nature.…”
mentioning
confidence: 99%
“…2,3 Collision with an object resulting in a dashboard injury or any traffic accident resulting in a kneeling injury on the ground are typical mechanisms. 4 There are urban centers in South Korea and China that treat a relatively high volume of isolated high-grade PCL injuries (including tibial PCL avulsions) with correspondingly a high output of isolated PCL surgical outcome studies in the past decade. 5 The hospital center represented in the article "Arthroscopic Treatment of a Tibial Avulsion Fracture of the Posterior Cruciate Ligament With the Use of a Suspensory Device" 6 by Zheng, Hou, Zhang, Li, Zhou, Li, and Pan is based in Xuzhou, a large city in Eastern China.…”
mentioning
confidence: 99%